(untitled) (Physical Education, Health and Social Sciences, 2026)
Basmati rice, a premium aromatic variety central to the export economies of India and Pakistan (valued at US14.17 billion and US3.96 billion in 2024, respectively), faces severe productivity threats from soil salinity, which affects 20% of irrigated lands globally and causes annual losses of US27.2 billion. Traditional breeding’s slow cycles (6–10 years) hinder rapid adaptation, necessitating innovative approaches. This review explores the integration of CRISPR/Cas9-mediated genome editing targeting stress-responsive transcription factors (e.g., NAC, MYB, WRKY families) and negative regulators (e.g., OsARR1, OsARM1) to enhance ion homeostasis, osmotic adjustment, and early maturity with speed breeding (SB) protocols that compress generation times to 4–6 cycles per year via extended photoperiods (22h light/2h dark) and controlled environments. Case studies demonstrate successful introgression of Saltol QTL and editing of OsBADH2 for aroma retention, yielding salt-tolerant lines with EC thresholds up to 8–12 dS/m and 10–15% earlier maturity. Socio-economic analyses highlight potential yield gains of 20–30% in salinized regions, while regulatory frameworks in South Asia emphasize biosafety. This synergistic strategy accelerates climate-resilient Basmati development, ensuring food security and economic stability amid escalating environmental pressures.